An Investigation on Biological Efficacies of Fruits and Leaves of Ficus auriculata (Timilo) from Kanchanpur District, Nepal - Bhatt, Bishan Datt; Joshi, Dharma Raj (Amrit Research Journal, 2021)
Ficus auriculata is a native Asian plant found in the temperate, tropical and subtropical regions and has been commonly used in traditional medicine and as fodder in animal husbandry. The comparative antibacterial and antioxidant efficacies of leaves and fruits have been studied using their hexane, chloroform, ethyl acetate and methanol extracts. Phytochemical screening exhibited the presence of important secondary metabolites like alkaloids, carbohydrates, glycosides, flavonoids and tannins. Antibacterial activities of fruit and leaf extracts in different concentrations were studied against E. coli, S. aureus and S. typhi by agar well diffusion method. The highest inhibition was found to be in 1% methanol extracts of leaves and fruits with a zone of inhibition (ZOI) ± 16 mm against S. aureus followed by E. coli and S. typhi with ZOI ±14 mm. The crude and 50% extracts of various solvents of both fruits and leaves were found to be ineffective against bacteria. These results reveal that there is a significant antibacterial activity in methanol extract of both fruit and leaves, against gram-positive and gram-negative bacteria. The antioxidant activities of methanol extracts of fruits and leaves were studied by DPPH radical scavenging assay. The IC50 values of methanol extract of leaves and fruit for DPPH radical scavenging assay were found to be 114.84 μg/mL and 78.28 μg/mL, respectively. These results reveal that methanol fruit extract exhibits better antioxidant activity as compared to the leaves. The result of this investigation has revealed the applicability of this plant as a potential source of several bioactive compounds for the discovery of new and efficacious drugs in days to come.